Development of a multiplex microsatellite marker set for the study of the solitary red mason bee, Osmia bicornis (Megachilidae) - Jens Van Eeckhoven; Gavin J. Horsburgh; Deborah A. Dawson; Kathryn Mayer; Amanda Bretman; Elizabeth J. Duncan (Molecular Biology Reports, 2022)
Background Solitary bees, such as the red mason bee ( Osmia bicornis ), provide important ecosystem services including pollination. In the face of global declines of pollinator abundance, such haplodiploid Hymenopterans have a compounded extinction risk due to the potential for limited genetic diversity. In order to assess the genetic diversity of Osmia bicornis populations, we developed microsatellite markers and characterised them in two populations. Methods and results Microsatellite sequences were mined from the recently published Osmia bicornis genome, which was assembled from DNA extracted from a single male bee originating from the United Kingdom. Sequences were identified that contained dinucleotide, trinucleotide, and tetranucleotide repeat regions. Seventeen polymorphic microsatellite markers were designed and tested, sixteen of which were developed into four multiplex PCR sets to facilitate cheap, fast and efficient genotyping and were characterised in unrelated females from Germany (n = 19) and England (n = 14). Conclusions The microsatellite markers are highly informative, with a combined exclusion probability of 0.997 (first parent), which will enable studies of genetic structure and diversity to inform conservation efforts in this bee.